The European Central Bank : credibility, transparency, and centralization - Haan, Jakob de.; Eijffinger, Sylvester C. W.; Waller, Sandra (Cambridge, Mass. : MIT Press, 2005)
This book contains balanced study of the monetary policy mechanisms of the European Central Bank, focusing on the political economy aspects of its decision-making processes.Besides giving a detailed and generally favourable study of the status quo, the authors advocate a more complete and overt shift towards an inflation targeting strategy, a continuing focus on transparency and accountability, and greater centralisation of decision making, especially after the accession countries join the eurozone.
Includes bibliographical references and index.
gau 17/06/14
Loans
Keywords: European Central Bank; Banks and banking, Central -- European Union countries; Monetary policy -- European Union countries